(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article further emphasizes how cultural misunderstandings can lead to frustration and anxiety, ultimately hindering effective communication and learning. It offers practical insights into ways that educators and language programs can address these barriers, such as incorporating cultural competence training, fostering an inclusive classroom environment, and allowing space for learners to share their own cultural backgrounds.